2010
DOI: 10.1111/j.1365-2672.2010.04901.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prescribed cleaning and disinfectant use on microbial contamination in the home

Abstract: Aims:  To identify and quantify the presence of Escherichia coli, Staphylococcus aureus, Salmonella, hepatitis A and norovirus in households and to assess the effect of chlorine and quaternary ammonium–based disinfectants following a prescribed use. Methods and Results:  Eleven sites distributed in kitchen, bathroom, pet and children′s areas of two groups of 30 homes each: (i) a nonprescribed disinfectant user group and (ii) a disinfectant protocol user group. During the 6‐week study, samples were collected on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 25 publications
1
29
0
4
Order By: Relevance
“…Individuals conceivably could reduce their risk of acquiring E. coli from touchable sites by using hand sanitizers after exiting the restroom. Likewise, the community conceivably could benefit if disinfectant products were used to clean public restrooms for greater bio-burden reduction; however, personal hand hygiene remains crucial (33). Regarding the isolates' characteristics, many of these environmental E. coli strains were from phylogenetic group B2, contained multiple virulence genes, qualified molecularly as ExPEC, and/or represented classic human-associated lineages, such as STs 10, 14, 69, 95, 127, and 405 (34).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals conceivably could reduce their risk of acquiring E. coli from touchable sites by using hand sanitizers after exiting the restroom. Likewise, the community conceivably could benefit if disinfectant products were used to clean public restrooms for greater bio-burden reduction; however, personal hand hygiene remains crucial (33). Regarding the isolates' characteristics, many of these environmental E. coli strains were from phylogenetic group B2, contained multiple virulence genes, qualified molecularly as ExPEC, and/or represented classic human-associated lineages, such as STs 10, 14, 69, 95, 127, and 405 (34).…”
Section: Discussionmentioning
confidence: 99%
“…Another study in household kitchens and bathrooms found that a QAC wipe reduced total bacterial numbers by 99.9% overall (15). A study involving 30 households in Mexico showed that the use of a QAC product statistically significantly reduced the occurrence of Escherichia coli on countertops over the 5 weeks of the study (16). In a study conducted in an elementary school, the use of QACbased disinfectant wipes once a day on the desk of each student reduced absenteeism by almost 50% (17).…”
mentioning
confidence: 99%
“…A number of studies have shown that enteric and respiratory pathogens are capable of surviving from hours to months on fomites, depending on the numbers deposited, the type of microorganism, and the variable environmental conditions (10)(11)(12). Several studies have shown that inanimate surfaces found in day care centers (8,(13)(14)(15)(16)(17), schools (18), office buildings (19), homes (20)(21)(22)(23)(24)(25)(26)(27), public areas (28), or hospitals (12,(29)(30)(31)(32)(33) can be reservoirs for secondary modes of transmission, with contaminated hands playing a critical role as a route of exposure.…”
mentioning
confidence: 99%